2003
DOI: 10.1021/ol035468w
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[n]uril Analogues

Abstract: Molecular recognition and self-assembly in aqueous solution have experienced rapid growth in recent years. The use of -, -, and -cyclodextrins, calixarenes, and cyclophanes have served as the platforms for molecular recognition in aqueous solution. Recently, the investigation of an alternative platform based on cucurbituril has become the focus of several research groups. The rigid structure and capability of forming complexes with molecules and ions through hydrophobic, iondipole and hydrogen-bonding interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 35 publications
2
113
0
3
Order By: Relevance
“…Figure 1) [14][15][16][17]. Recently some efforts have been made to introduce substitution in order to achieve ready solubility in both aqueous systems and common organic solvents, and a number of fully and partially substituted Q[n]s have been reported [18][19][20][21][22][23]. Decamethylcucurbit [5]uril (Me 10 Q [5]) was the first fully substituted Q[n] discovered in 1992 by Stoddart and co-workers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1) [14][15][16][17]. Recently some efforts have been made to introduce substitution in order to achieve ready solubility in both aqueous systems and common organic solvents, and a number of fully and partially substituted Q[n]s have been reported [18][19][20][21][22][23]. Decamethylcucurbit [5]uril (Me 10 Q [5]) was the first fully substituted Q[n] discovered in 1992 by Stoddart and co-workers [19].…”
Section: Introductionmentioning
confidence: 99%
“…A basicidade destes compostos é bastante baixa sendo verificados pKa's do ácido conjugado do CB [6] da ordem de 3, sendo desconhecida para os outros cucurbitandos. Uma das estratégias para contornar o problema de solubilidade é a utilização de meios salinos ou ácidos para aumentar a solubilidade destes compostos pela formação de complexos com ácidos duros ou, ainda, pela protonação das carbonilas dos opérculos destas estruturas 12 4,7,[16][17][18][19][20][21][22][23][24][25][26][27] . A reação de CB [6], por exemplo com K 2 S 2 O 8 , dá origem a 12 grupos OH radiais nos carbonos terciários em meio aquoso 22,28 , enquanto que a utilização de dimetil glicolurila como monômero precursor dá origem à decametil-CB [5] …”
Section: Síntese E Propriedades Físico-químicasunclassified
“…The chemistry of cucurbit[n]uril (Q[n]s) has expanded dramatically with the discovery of cucurbituril(Q [6]) and its homologues (Q [5], Q [7], Q [8], and Q [10]) [1][2][3]. Recently, the direct functionalization of CB[n] [4][5][6] and introduction of building blocks for the preparation of Q[n] derivatives [7][8][9] and analogues [10][11] providing CB[n]s with solubility in both organic and aqueous solution has further expanded the range of the research and applications, which have been summarized in related reviews [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the direct functionalization of CB[n] [4][5][6] and introduction of building blocks for the preparation of Q[n] derivatives [7][8][9] and analogues [10][11] providing CB[n]s with solubility in both organic and aqueous solution has further expanded the range of the research and applications, which have been summarized in related reviews [12][13][14][15][16][17][18][19]. More recently, we have found that the solubilities of substituted cucurbit[n]urils (SQ[n]s) are dependent upon the kind, position and number of substituent groups on the substituted cucurbit[n]urils Q[n]s [20].…”
Section: Introductionmentioning
confidence: 99%